Auditorium Building (later old Meany Hall), University of Washington, probably between 1911 and 1912 (1911)
The Auditorium Building was built for the 1909 Alaska-Yukon-Pacific Exposition where it was used for concerts, speeches and other gatherings. In 1914 after the Exposition, the building was renamed Meany Hall. Written on photograph: The Assembly Hall, Washn University, Seattle. PH Coll 1610.3